2000
DOI: 10.7863/jum.2000.19.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric fistula: evaluation with ultrasonography.

Abstract: Twenty‐two patients with 24 fistulae were examined prospectively with real‐time sonography. Sonographic findings were compared with those of intravenous urograms and correlated with the findings at examination under anesthesia and at surgery. Various genital abnormalities not revealed by intravenous urography were demonstrated by sonography preoperatively. These included cervical injuries, vesicovaginal fistula showing "flat tire" sign and hourglass deformities, and identification of the site, size, and course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…A high creatinine level of the discharge can confirm the urinary leakage. However, intravenous pyelography and cystogram may not demonstrate the genital abnormalities [12]. The advanced but more invasive and/or costlier techniques include combined vaginoscopy-cystoscopy [13], subtraction magnetic resonance fistulography [14] (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…A high creatinine level of the discharge can confirm the urinary leakage. However, intravenous pyelography and cystogram may not demonstrate the genital abnormalities [12]. The advanced but more invasive and/or costlier techniques include combined vaginoscopy-cystoscopy [13], subtraction magnetic resonance fistulography [14] (Fig.…”
Section: Diagnosismentioning
confidence: 99%
“…Some other studies have reported the prevalence of secondary amenorrhoea in clients with obstetric fistula to be between 25% -63.1% and in this study, the overall rate of secondary amenorrhoea was 32% [8][9][10][11][12]. It was interesting to note however that the fistula survivors with childbirth had a statistically significant lower rate of amenorrhoea than the rest of the study population [12].…”
Section: Discussionmentioning
confidence: 50%
“…Some studies have highlighted the gynaecologic injuries associated with obstetric fistula to include vaginal scarring and a sonographic study from Nigeria had detected vaginal fibrotic changes in 32% of clients and minor vaginal fibrosis in 36% of cases [9]. There is no doubt that vaginal scarring will impact on sexual function and the functionality of the vagina which is an important concern in normal healthy marital relationships may assumably play a role in the reported high rates of marital separation among women with obstetric fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Transabdominal ultrasound evaluation of urogenital fistulae, supported poorly by the limited data available has shown variable sensitivity in the diagnosis of genitourinary fistulae, with some case reports reporting positive identification of fistula in as low as 29% of cases. 8 The ultrasound done in this case was essentially normal. The available data on MRI diagnosis of VUF is very limited.…”
Section: Discussionmentioning
confidence: 71%